Analisis Faktor yang Berhubungan dengan Status Gizi Anak Usia 6-59 Bulan - Suzanna Suzanna; Indah Budiastutik; Marlenywati Marlenywati (Jurnal Vokasi Kesehatan, 2017)
Abstract: Analyze Factors Related To The Nutrional Status On Children Aged 6-59 Months. Nutritional problem among infants is considered as the main health issue. Children under the age of 5 regarded to vulnerable age group. This study aimed at figuring out the  factors related to nutritional status of children aged 6-59 months at publich health centre in North Singkawang in Singkawang city. Cross sectional approach was carried out in this study. As many as 96 children aged 6-59 months were employed as the samples.  This study was conducted from March to may 2014. Meanwhile, proportional random sampling was utilized as the data collection technique. Then, the data were statistically analyzed by using chi square test.The study revealed were significant correlation of maternal education (p value=0,000), maternal nutritional knowledge (p value=0,022), parenting styles (p value=0,000), infectious disease (p value=0,000), energy intake (p value=0,000), protein consumption (p value=0,000), and nutritional status of children aged 6-59 months at publich health centre in Singkawang Utara. There were correlation of maternal age during pregnancy (p value= 0,877), number of children (p value=0,938), eating pattern p value=0,688), and nutritional status of children. Suggestion As a result, local institutions and public health centers are encouraged to enhance  health information, particularly infants nutrition. Therefore, mothers with children under the age of 5 become aware of the nutritional status of their children.Abstrak: Analisis Faktor Yang Berhubungan Dengan Status Gizi Anak Usia 6-59 Bulan. Masalah gizi masih merupakan masalah kesehatan terutama anak balita, karena balita merupakan kelompok rawan. Penelitian bertujuan mengetahui faktor-faktor yang berhubungan dengan status gizi anak usia 6-59 bulan di Puskesmas Kecamatan Singkawang Utara Kota Singkawang. Penelitian menggunakan desain cross sectional dengan jumlah sampel 96 balita usia 6-59 bulan yang dilaksanakan bulan Maret sampai dengan Mei 2014. Teknik pengambilan sampel proporsional random sampling. Pengolahan dan analisa data menggunakan komputerisasi. Uji statistik yang digunakan uji chi square.Ha sil penelitian menunjukkan ada hubungan yang bermakna antara pendidikan ibu (p value=0,000), pengetahuan gizi ibu (p value=0,022), pola asuh (p value=0,000), penyakit infeksi (p value=0,000), asupan energi (p value=0,000) dan asupan protein (p value=0,000) dengan status gizi balita di Puskesmas Kecamatan Singkawang Utara Kota Singkawang dan tidak ada hubungan yang bermakna antara umur ibu saat hamil (p value=0,877), jumlah anak (p value=0,938) dan pola makan (p value=0,668) dengan status gizi balita.Disarankan pada ibu yang memiliki balita untuk bisa lebih meningkatkan pengetahuan melalui membaca buku menu seimbang dan media informasi seperti televisi, majalah, internet dll. Serta meningkatkan konsumsi Energi sebanyak 1600 gr/hr, Protein sebanyak 35 gr/hr (AKG, 2013).